2022
DOI: 10.1192/bjo.2022.48
|View full text |Cite
|
Sign up to set email alerts
|

Psychological predictors of insomnia, anxiety and depression in university students: potential prevention targets

Abstract: Background Perfectionism, low self-esteem and external locus of control are psychological constructs linked to insomnia, anxiety and depression. Examining how these constructs impact mental health and serve as risk factors for the development of clinically significant symptoms may help direct psychological support resources and preventative measures for university students. Aims To longitudinally examine associations between the aforementioned psychological constructs and symptoms of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…Second, consistent with our frst hypothesis, NRS was positively associated with emotional distress, which was also confrmed in a previous study [60]. In a two-year longitudinal study, NRS was found to have the ability to predict long-term depression [61].…”
Section: Discussionsupporting
confidence: 89%
“…Second, consistent with our frst hypothesis, NRS was positively associated with emotional distress, which was also confrmed in a previous study [60]. In a two-year longitudinal study, NRS was found to have the ability to predict long-term depression [61].…”
Section: Discussionsupporting
confidence: 89%
“…Robust evidence demonstrates that cognitive behavioral therapy is effective in managing acute insomnia symptoms [ 18 , 45 ]. Lindsay and his colleagues have found that the external locus of control is a psychological construct linked to insomnia [ 63 ]. Individuals with a high level of hope may move from the external locus of control to the internal–external locus of control to encourage them to think about the goal and the corresponding pathway and then increase their control.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with a reported increase in screen-positive rates of anxiety and depressive symptoms over the academic year in undergraduates. 4 A contributing factor underlying these trends may be increasing levels of stress as academic pressures and responsibilities mount, and final examinations draw closer. 32 Examination-related anxiety can manifest in many ways, including disrupted sleep and increased fatigue.…”
Section: Discussionmentioning
confidence: 99%
“… 1 In 2018, approximately 18% of first-year undergraduates at Queen's University, Canada (12% of men and 20% of women) reported sleep difficulties indicative of probable insomnia at school entry. 2 Insomnia in university students is associated with reduced academic performance, 3 , 4 and common mental health concerns such as anxiety and depression. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%